A historical-cultural approach to physics teaching : analysis and proposal of a didactic sequence - Galbiatti, Douglas Augusto [UNESP]; Camargo, Eder Pires de [UNESP] (Organizacion Estados Iberoamericanos Educacion Ciencia & Cultura-oei, 2016)
Is analyzed in this article a didactic sequence developed during a master's research. The didactic sequence in question, together with five experimental assemblies composed a teaching approach designed and implemented by the researcher with students of a degree course in Physics of a Brazilian public university. The activities of that research were carried out according to the steps ordered in didactic sequence, so that each step served as directional agent of actions taken by the researcher. The methods of this qualitative research were conducted through recording in audio and video, the meetings that the researcher conducted with the subjects, which allowed the subsequent transcription and analysis of activities. The results pointed towards the conceptual evolution of the thinking of individuals with regard to the concepts studied, thus indicating the potential and the limits of the activities performed. We aim through of that exposure, present and analyze the results generated by the application, as well as raise the possible use of this sequence by teachers of different educational levels.
Keywords: physics teaching; cultural-historical theory; teaching approach; didactic sequence